DEVELOPMENT OF AZITHROMYCIN LOADED LEMONGRASS OIL BASED MICROEMULSION AND DETERMINATION OF ANTIBACTERIAL POTENTIAL - Ebenazer, Andrew; Franklyne, Jonathan Sampath; Mukherjee, Amitava; Chandrasekaran, N. (International Journal of Applied Pharmaceutics, 2018)
Objective: Azithromycin (AZM), an azalide drug is used to treat bacterial infections. It is poorly water-soluble, with low human bioavailability due to partial absorption. This can be improved using a microemulsion drug delivery system using essential oil. Methods: Microemulsion system was prepared with AZM solubilized lemongrass oil (Cymbopogon citratus), Tween 20 and water containing 1% (v/v) 10 mmol sodium hydroxide. In vitro drug release was determined using a 14KDa semipermeable dialysis membrane. The kinetics of bacterial killing was done at MIC concentrations, and viable counts were determined hourly for 24 h. Bacterial cell viability was determined by differential staining with acridine orange and ethidium bromide. In vitro toxicity was determined by the MTT assay, while in vivo toxicity was determined in male Wistar rats. Results: The optimized formulation (5:20:75 %) was thermodynamically stable with drug solubility of 366.90 mg/ml and a droplet diameter of 12.4Â±3.9 nm, which do not show in vivo or in vitro toxicity. In vitro drug release study in simulated body fluids revealed a controlled drug release from microemulsion-based formulation. The MIC was 1Î¼g/ml and 2Î¼g/ml against Staphylococcus aureus and Escherichia coli respectively. In vitro kill kinetics showed>2 log10 killing by 8 h. Bacterial cell viability assay and scanning electron microscopy analysis further confirmed substantial morphological changes due to alteration in the cell membrane. Conclusion: The reduced droplet size and the inherent antibacterial property of lemongrass oil enhanced the efficacy of the AZM loaded ME system in comparison with the bulk drug, against the bacterial pathogens.